2015
DOI: 10.1017/s1743923x15000495
|View full text |Cite
|
Sign up to set email alerts
|

Encouragement is not Enough: Addressing Social and Structural Barriers to Female Recruitment

Abstract: Invite a woman to run for office. Based on findings that women are most responsive to and reliant on encouragement in making the decision to run for office, this invitation refrain is pervasive among those seeking greater gender parity in U.S. politics. For example, in 2007, the Women's Campaign Fund launchedShe Should Run, complete with an online tool that, to date, has been used to ask just under 200,000 women to run for office. In 2014, another organization, Vote Run Lead, adopted a similar strategy, launch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 5 publications
0
37
0
1
Order By: Relevance
“…Gender and political recruitment studies have shown that 'male homosocial capital', based on 'expressive' resources such as likeability and trust as well as 'instrumental' resources like in-group networking and linkage to party selectors, provides men with a strong advantage in candidate selection processes (Bjarnegård 2013). Party selectors -mostly men -tend to encourage men to run more often than women, with political experience not necessarily integrating the criteria used to recruit 'in-group' members (Cheng & Tavits 2011;Dittmar 2015;Lawless & Fox 2010;Niven 1998). Rather, as posited by Murray (2014: 522, 530), whereas 'men may themselves be accessing politics on the basis of their sex rather than their more tangible qualities … women have to be exceptional to overcome social, structural, and political barriers to office' .…”
Section: Individual Factorsmentioning
confidence: 99%
“…Gender and political recruitment studies have shown that 'male homosocial capital', based on 'expressive' resources such as likeability and trust as well as 'instrumental' resources like in-group networking and linkage to party selectors, provides men with a strong advantage in candidate selection processes (Bjarnegård 2013). Party selectors -mostly men -tend to encourage men to run more often than women, with political experience not necessarily integrating the criteria used to recruit 'in-group' members (Cheng & Tavits 2011;Dittmar 2015;Lawless & Fox 2010;Niven 1998). Rather, as posited by Murray (2014: 522, 530), whereas 'men may themselves be accessing politics on the basis of their sex rather than their more tangible qualities … women have to be exceptional to overcome social, structural, and political barriers to office' .…”
Section: Individual Factorsmentioning
confidence: 99%
“…Women may be particularly vulnerable to campaign attacks. Although being asked to run has been shown to increase women's political ambition, they are less likely to respond positively to recruitment than their male counterparts . Compared with men, women need more encouragement to enter politics and must be asked to run, but they receive less encouragement, are asked less frequently, and are less likely to respond positively when they are asked …”
Section: Why Don't We Have Women?mentioning
confidence: 99%
“…Men are twice as likely as women to consider themselves qualified, even when their qualifications are objectively the same . Societal expectations regarding childrearing and obligations to extended family delay the political careers of politically ambitious women, as concerns about balancing their personal lives with campaign demands inhibit willingness to run . Friends and family are less likely to encourage women to run for office, compared with men .…”
Section: Why Don't We Have Women?mentioning
confidence: 99%
“…As clear as these national trends may be, candidates also need to weigh a wide range of more personal and local considerations. These factors may include the availability of volunteers and donors (Kanthak and Woon, ; Kitchens and Swers, ), the absence or presence of party networks (Crowder‐Meyer, ; Dittmar, ; Sanbonmatsu, ), and, particularly relevant for this analysis, the range of available opportunities in the area (Sanbonmatsu, ). In a state such as Washington—a Democratic state that falls above national medians in affluence and education, and has a wealth of women role models in both the national and state legislatures—a potential woman candidate's national, local, and personal evaluations may all lead to the same conclusion: the costs of running for office are relatively low and the probability of victory is relatively high.…”
Section: Candidate Emergence and Successmentioning
confidence: 99%